(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article aims to analyze the influence of the management team on promoting motivation and emotional intelligence in the school context. The research, which uses a qualitative approach and bibliographical content, is based on contemporary studies that discuss the role of school management in building a balanced, welcoming, and conducive educational environment for human development. The analysis highlighted that the management team’s role goes beyond administrative functions, being essential for creating emotional bonds, encouraging teacher autonomy, strengthening a sense of belonging, and mediating interpersonal relationships. Educational leadership, when guided by humanizing values, is better able to face contemporary school challenges, acting with empathy, active listening, sensitivity, and conflict resolution skills. It was observed that managers who develop and encourage socio-emotional practices foster the intrinsic motivation of teachers and students, which directly impacts the quality of teaching and learning. Furthermore, it was found that emotional intelligence applied to school management strengthens institutional culture and contributes to the creation of more just, democratic, and collaborative environments. Valuing the emotional aspect in the daily life of schools, combined with ongoing training for educational leaders, represents a determining factor in fostering a healthier organizational climate focused on meaningful learning. It is concluded that strengthening motivation and emotional competencies, when intentionally promoted by the management team, expands the possibilities for transforming the school into a more humane, sensitive, and inclusive space.